Unsupervised classification techniques for determination of storm region correspondences - Parikh, Jo Ann; DaPonte, John S.; Vitale, Joseph N. (Applications and Science of Computational Intelligence II, 1999)
The objective of this study is to compare statistical and unsupervised neural network techniques for determination of correspondences between storm system regions extracted from sequences of satellite images. Analysis was applied to the International Satellite Cloud Climatology Project (ISCCP) low resolution D1 database for selected storm systems during the period April 5 - 9, 1989. Cloud top pressure was used to delineate regions of interest and cloud optical thickness combined with spatial location was used to track regions throughout a given time sequence. The ability of the k-nearest neighbor classifier and of self-organizing maps to determine correspondences between storm regions was assessed. The two techniques generally yielded similar associations between regions of interest throughout the time sequence. Differences in final tracking results between the two techniques occurred primarily as a result of differences in the collections of points from a region in a time step t2 that corresponded to a region in an earlier time step t1. The tracking results were also compared to the results obtained at the NASA Goddard Institute for Space Studies using sea level pressure data from the National Meteorological Center (NMC). For the storm systems investigated in this study, the storm tracks exhibited the same general tracking behavior with expected variations between cloud system storm centers and low sea level pressure centers.
Keywords: Algorithms; Climate change; Climatology; Feature extraction; Image processing; Mapping; Nearest neighbor classifier; Neural networks; Self organizing map; Storm tracking; Storms; dept.csc; ⛔ No DOI found